Modulating Technology for Scroll Compressor with Refrigerant Release - Wang Baolong Han Linjun Shi Wenxing Li Xianting (Zhileng xuebao)
The inner volume efficiency of constant-volume-ratio compressors declines fast when the difference between indoor temperature and outdoor temperature decreases,especially for the refrigeration(heat pump) systems used in air-conditioning,leading to the poor performance of these systems.In addition,with the decrease of the compression ratio,the heating/cooling requirement drops,but the heating/cooling capacity of the refrigerating system rises.In our research,a novel scroll compressor refrigeration system wit...